2013
DOI: 10.5114/ninp.2013.34398
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of concomitant and adjuvant temozolomide in glioblastoma treatment. A multicentre randomized study

Abstract: The introduction of TMZ before, during and after radiotherapy for newly diagnosed glioblastoma multiforme gives clinically and statistically significant improvement of survival with unremarkably increased toxicity of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Stupp et al [14] demonstrated that a combination of TMZ with postoperative radiation prolonged the overall survival compared to radiation alone. This was supported by subsequent reports, where TMZ before, during and after RT provided clinically and statistically significant improvements in patients with newly diagnosed GBM [15,16,17]. Comparison of studies before (2000-2003) and after (2005-2008) the introduction of TMZ revealed that patients treated with surgery and radiation had a median survival of 12 months, while those treated with TMZ had a median survival of 14.2 months [6].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Stupp et al [14] demonstrated that a combination of TMZ with postoperative radiation prolonged the overall survival compared to radiation alone. This was supported by subsequent reports, where TMZ before, during and after RT provided clinically and statistically significant improvements in patients with newly diagnosed GBM [15,16,17]. Comparison of studies before (2000-2003) and after (2005-2008) the introduction of TMZ revealed that patients treated with surgery and radiation had a median survival of 12 months, while those treated with TMZ had a median survival of 14.2 months [6].…”
Section: Introductionsupporting
confidence: 64%
“…Of the remaining 42 articles, 30 were non-randomized studies, 1 was duplicate study, 3 did not report an outcome of interest, 1 did not analyze concomitant TMZ + RT and the full text was not available for 1 article. Thus, 6 eligible studies (5 trials) [13,14,15,17,23,24] were included in this meta-analysis. The flow chart describing the selection of trials is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the treatment options for recurrent cases include systemic, re-irradiation, and second surgery in order to improve outcomes. The risks and benefits of radiation, chemotherapy, and surgical extent in GBM patients have been assessed in numerous studies (6)(7)(8)(9). However, the value of surgical extent in elderly patients with high-grade glioma remains unestablished.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is also with limited effects, since most chemicals have difficulty in crossing the blood brain barrier [4]. Temozolomide is the most effective chemotherapeutic reagent but can usually prolong the lifespan for only 3–6 months in some patients [5, 6], with side effects. Novel therapy approaches include combinations of molecular targeted agents such as epidermal growth factor receptor, vascular endothelial growth factor receptor, and mammalian target of rapamycin.…”
Section: Introductionmentioning
confidence: 99%